Identification of Urban Ecological Security Pattern Based on Ecosystem Services Supply–Demand - Huayan Liu; Jianhua Zhu; Lixiong Zeng; Mengmeng Gou; Beiling Chen; Jinxia Lv; Wenfa Xiao (Ecosystem Health and Sustainability, 2024)
The construction of ecological security pattern (ESP) is an effective way to ensure regional ecological security. Although the method of constructing the regional ESP based on ecosystem services (ESs) has been widely recognized and applied, the spatial characteristics of ESs supply–demand mismatch has not been well included into ESP construction. We constructed a regional ESP framework connecting demand sources and ecological sources from the perspective of ESs supply–demand mismatch. Taking the Wuhan urban agglomeration (WUA), findings indicated distinct spatial aggregations of ecological sources and demand sources due to the supply–demand mismatch of ESs. Ecological sources (12,406.29 km2 or 21.42%) were primarily located in the south and north of WUA, while demand sources (1,191.26 km2 or 2.07%) were concentrated mainly in the central. Two types of corridors jointly ensured regional ecological security. A total of 86 supply–supply corridors in the north ensured the supply ability of ESs by connecting ecological sources, while 35 supply–demand corridors in the south alleviated the supply–demand mismatch of ESs. The targeted implementation of ecological governance based on the corridor types provides a new approach to coordinate the mismatch of ESs supply–demand and enhance ecological security. However, 63.38 km2 of pinch points, recognized as high-flow areas within the corridors, primarily comprised fragmented landscapes, and barriers covering 99.67 km2 obstructed corridor flow, notably surrounding the demand sources. These regions should be prioritized for ecological conservation. Overall, this research framework provides a reliable scientific basis for configuring spatial landscape patterns and developing ecological strategies in urban agglomerations.